2020
DOI: 10.1182/blood.2019003507
|View full text |Cite
|
Sign up to set email alerts
|

Erdheim-Chester disease: consensus recommendations for evaluation, diagnosis, and treatment in the molecular era

Abstract: Erdheim-Chester disease (ECD) is a rare histiocytosis that was recently recognized as a neoplastic disorder owing to the discovery of recurrent activating MAPK (RAS-RAF-MEK-ERK) pathway mutations. Typical findings of ECD include central diabetes insipidus, restrictive pericarditis, perinephric fibrosis, and sclerotic bone lesions. The histopathologic diagnosis of ECD is often challenging due to nonspecific inflammatory and fibrotic findings on histopathologic review of tissue specimens. Additionally, the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
366
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 247 publications
(467 citation statements)
references
References 100 publications
7
366
0
14
Order By: Relevance
“…This report followed Strengthening the Reporting of Observational Studies in Epidemiology ( STROBE ) reporting guideline. Patients were enrolled between January 2011 and December 2018, and the diagnosis was established based on ECD consensus criteria 2 , 19 and verified with history, physical examination, and laboratory, genetic, and imaging investigations, as previously reported. 14 ECD biopsy samples (common sites, perinephric or retroperitoneal tissue, bone and skin) were reviewed by a certified pathologist who confirmed the diagnosis of ECD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This report followed Strengthening the Reporting of Observational Studies in Epidemiology ( STROBE ) reporting guideline. Patients were enrolled between January 2011 and December 2018, and the diagnosis was established based on ECD consensus criteria 2 , 19 and verified with history, physical examination, and laboratory, genetic, and imaging investigations, as previously reported. 14 ECD biopsy samples (common sites, perinephric or retroperitoneal tissue, bone and skin) were reviewed by a certified pathologist who confirmed the diagnosis of ECD.…”
Section: Methodsmentioning
confidence: 99%
“…While the incidence and prevalence of ECD is unknown, the medical literature contains a few hundred cases of ECD, which is characterized by male predominance and a mean age at presentation of 53 years. 1 , 2 Initially described by Erdheim and Chester in 1930 as lipoid granulomatosis, the disorder was reclassified in 2016 by the World Health Organization as a neoplasm of histiocytic origin, characterized by lipid-rich foamy macrophages infiltrating various organs. 3 , 4 , 5 Genetic perturbations in key molecular pathways, including BRAF V600E (OMIM 164757 ) and mitogen-activated protein kinase (MAPK), occur in a subset of hematopoietic cells and cause enhanced proliferation and increased survival of monocytic cells.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent trial of cobimetinib for histiocytic neoplasms, an overall response rate of 89% was observed by mPERCIST, compared with an overall response rate of 57% by RECIST, suggesting that [18]F-FDG PET/CT more readily detects response to treatment. The broad recommendation for implementation of [18]F-FDG PET/CT for response assessment in ECD [30] and other histiocytosis [31] reflects a belief among experts that metabolic assessment is useful to gauge response to treatment and that favorable metabolic response reflects a clinical benefit from treatment, but this has not been proven in ECD. There are limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…20% of ECD patients may have mixed histiocytosis with simultaneous Langerhans cell histiocytosis lesions, which can be even identified in the same biopsy. [9,10] Moreover, the ECD histiocytes share the same morphological and immunohistochemical profile of the juvenile xanthogranuloma (JXG). Therefore, it has been postulated that ECD is a variant of a non-cutaneous JXG.…”
Section: Discussionmentioning
confidence: 99%
“…However, for ECD patients without BRAF V600 mutation, it is recommended to continue Next-generation Sequencing (NGS) to identify other MAPK-ERK pathway alterations. [9,15]…”
Section: Discussionmentioning
confidence: 99%